2014
DOI: 10.1186/1471-2458-14-739
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-related psychosocial impact of patients with genital warts in China: a hospital-based cross-sectional study

Abstract: BackgroundGenital warts (GW) are the most common sexually transmitted infections. To date, few studies using a human papillomavirus (HPV)-specific questionnaire have focused on the impact of quality of life (QoL) among patients with GW in developing countries. The origins of GW related psychosocial burdens and variations between genders were poorly characterized as well.MethodsA hospital-based survey was conducted in Beijing and Nanjing of China in 2008. Eligible patients aged 18–65 who had a diagnosis of GW w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 13 publications
4
44
0
5
Order By: Relevance
“…26 Thus, one of the most significant characteristics found in women diagnosed with HPV is the genital change, which may not only cause pain and bleeding in sexual intercourse but also shame and embarrassment, which could lead to marital problems. 17,27,28 Thus, legitimating the findings of the present study, the distrust and the risk of infidelity were also pointed out by Jeng et al 29 as possible causes of conflict with the partner because they believed that alleged extramarital affairs could be the source of the infection.…”
Section: Discussionsupporting
confidence: 63%
“…26 Thus, one of the most significant characteristics found in women diagnosed with HPV is the genital change, which may not only cause pain and bleeding in sexual intercourse but also shame and embarrassment, which could lead to marital problems. 17,27,28 Thus, legitimating the findings of the present study, the distrust and the risk of infidelity were also pointed out by Jeng et al 29 as possible causes of conflict with the partner because they believed that alleged extramarital affairs could be the source of the infection.…”
Section: Discussionsupporting
confidence: 63%
“…The HIP questionnaire was developed recently, which specifically evaluated the psychosocial burden of HPV. Previous researchers (Wang et al 2010, Qi et al 2014, have undertaken studies in Chinese women residing in Taiwan and mainland using a Chinese version of the HIP. The HIP contains seven functional constructs with 29-items: worries and concern (nine items), emotional impact (five items), sexual impact (two items), self-image (four items), partner issues and transmission (three items), interactions with doctors (three items) and control/life impact (three items).…”
Section: Psychosocial Impact Of Hpv Infectionmentioning
confidence: 99%
“…With an overall prevalence rate of around 1-5%, they are one of the most common sexually transmitted infections [2]. AGWs are usually asymptomatic, but they can be painful or pruritic and can cause significant psychosocial distress depending on size and location [3,4]. Numerous HPV vaccination campaigns have been conducted, but few studies have demonstrated their efficacy in reducing the number of AGWs [5].…”
Section: Introductionmentioning
confidence: 99%